Conquering RAS : from biology to cancer therapy - Azmi, Asfar S. (Academic Press is an imprint of Elsevier, 2017)
Conquering RAS: From Biology to Cancer Therapy provides introductory knowledge on how modern RAS biology is taking shape in light of newer technological development. Each chapter is written in a manner that emphasizes simplicity and readability for both new investigators and established researchers. While RAS biology has been intensively studied for more than three decades, we are yet to see any effective therapeutics that could interfere in the signaling cascade regulated by this master oncogene. The book covers topics ranging from basic RAS biology, to translational biology and drug discovery applications. These topics will be appealing to basic researchers working in labs who seek deeper understanding of the modern concepts in RAS research. On the other side, the oncologist at the patient's bedside will find the book useful as they routinely face the daunting task of treating patients that predominantly have a disease driven by oncogenic KRAS. Brings together wide ranging topics in RAS basic and translational biology for the scientific and clinical communities. Showcases recent advancements in RAS research under one comprehensive volume. Includes video clips, color illustrations, and important website links to facilitate a clear understanding of RAS in cancer research.